The impact of new technologies on the cruise travelers experience: A literature review - Gonzáles-Santiago, M.; Loureiro, S. M. C.; Langaro, D. (14th Annual Conference of the EuroMed Academy of Business, Book of Proceedings, 2021)
Companies around the world have been adopted different digital technologies such as online stores, digital panels, or even robotic assistance. These new technologies have also impacted the cruise industry, that is one of the fastest-growing sectors within the hospitality and tourism industry (Penco et al., 2019; Shoval et al., 2020). So, cruise companies are developing new technological ships using different digital technologies onboard such as Artificial Intelligence (AI) or Virtual Reality (VR). As an example of the adoption of this technologies, AI can be found in the Royal Caribbean's bionic bar that uses service robots (Lu et al., 2019), in the latest MSC cruise ships that implemented a digital assistance called ZOE that assist onboard guest with reservation, inquires, and learn their preferences (Shallo, 2019; MSC Cruises, 2021), or even through online purchases that delivered the items to guest staterooms on the newest Celebrity Cruises ships (Maddox, 2019; Celebrity Cruises, 2020). On the other hand, VR is mainly used by cruise companies in areas such as shore excursions or culinary dining (Arlati et al., 2018; Loureiro et al., 2019). This denotes, that cruise companies are adopting these technologies to provide a new and better experience to their cruise travelers, as most of them use technologies in their daily lives activities and hope to find them also when they travel (CLIA, 2019). Indeed, the acceptance and use of these new technologies will depend on the technological readiness of the consumer (Blut and Wang, 2020). In addition, when consumers interact with these technologies it can lead them to an emotional reaction, that can influence their behavioral responses (Gao and Bai, 2014). This emotional reaction is also known as an online flow state, which has been defined by Novak et al. (2000) as the state occurring during network navigation. Also, literature in the hospitality, tourism, and technology industry reveals that further studies need to be done within cruise tourism and technologies (Lu et al., 2019; Loureiro et al., 2020). Therefore, this abstract paper is an integration of three different theories: S–O–R framework (Donovan and Rossiter, 1982), E-servicescape (Harris and Goode, 2010), and Flow experience (Gao and Bai, 2014), since with the S–O–R model the purpose of this paper is to explain how the E-servicescape environment on cruise ships (S), can lead to an emotional reaction of cruise ship travelers presented as a flow experience (O), and how this emotional reaction can influence the behavioral response of the cruise travelers (R) in relation to the intention of use technological devices onboard the cruise ship and purchase intention. As far as we know, this is the first time in the literature of the Hotel and Tourism Industry and also of the Technology Industry that this research is been conducted since most recent studies have been made in hotels, restaurants, and airports (Bogicevic et al., 2017; Li, Bonn and Ye, 2019; de Kervenoael et al., 2020; Hou, Zhang and Li, 2021). Therefore, the expected research result of the project aims to provide some theoretical contributions in the literature of Tourism and Technology, as stated above, the present literature has some gaps between these industries. In addition, we also hope that these contributions can help future researchers in their projects related to these topics. Additionally, the results obtained will provide some practical contributions to cruise companies, cruise ship managers, and marketers, as they can take into consideration the results that can allow them to have a better insight of the cruise traveler’s reaction towards the future technologies implemented on their new ships.